ANALYZING THE ENTREPRENEURIAL SELF-EFFICACY ON ONLINE FLORIST IN MANADO - Mekel, Valentine; Massie, James D.D; Pandowo, Merinda H.C (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2019)
Abstract: In Manado, Capital City of Sulawesi Utara, there are few Online Florist also, starts from SJ Buckets, Tarloda Florist, Eskali Flowers, and many more. The quality of the products itself is really great and can be compared with online florist that came from outside Manado such as Jakarta and Bandung. By examining through Entrepreneur Self-Efficacy Scale, the Self-efficacy can be task specific, and entrepreneurship involves performance across multiple areas where by the individual needs a broad set of skills. Thus, by measures ESE across multiple dimensions is a more precise measure and can unveil more specific information to pinpoint weaknesses that could hinder more success of Online Florist Market in Manado that keeps developing more and more each day. This research aims to see the Entrepreneurial Self-Efficacy on Online Florist in Manado. The result shows that most of the respondent or informant uses personal funds to open their business and most of the respondent or informant tends to focus on the main product for the development. Recommendation for this research are Business owner should make add-on product that can support sales of their main product and Business owner should collaborate more instead just competing in order to survive together.Keywords: entrepreneurial self-efficacy, online marketing, marketing mix.